Sentidos atribuídos à sala de apoio e às dificuldades de aprendizagem da matemática por alunos do 5° ano do ensino fundamental em escolas municipais de Cuiabá - MT - Teles, Mariana Honório de Alencastro (2020)
This research developed in the line of research in Science Education and Mathematical Education PPGE / UFMT, seeks to answer the problem: What meanings do students in the 5th year of elementary school from two municipal schools sent to the support room attribute to this formative space, their learning and difficulties with mathematics? In this way, we outlined as a general objective to investigate the meanings attributed by students about the teaching and learning processes of mathematics experienced in the school space, specifically in the learning support room. And as specific objectives, to identify the guidelines of the conducting teachers about the students' learning difficulties in mathematics; characterize students sent by teachers to the support room considered to have difficulties in learning mathematics; analyze the meanings that students attribute to mathematics classes and their own learning; analyze the meanings that students attribute to pedagogical work with mathematics experienced in the context of the support room. We report on the theoretical references that deal with school organization in human formation cycles, concepts of teaching and learning, mathematical education and difficulties in learning mathematics. To develop the research, we are guided by the qualitative approach, of the exploratory type. Six (06) students enrolled in the 5th year of the second cycle of elementary school participated in the research, sent by their teachers to the Learning Support Room. For the production of information, school documents, questionnaires, the researcher's field diary were used and as a procedure, narrative interviews with participating students. From the theoretical framework and the production of information, four axes of analysis emerge: the context of the Learning Support Rooms (SAA), characterization of students sent by teachers to the support room considered to be in difficulties in learning Mathematics, the meanings attributed by students sent to the Mathematics support room and their own learning and the meanings that students attribute to the pedagogical work of Mathematics experienced in the context of the learning support room. The results indicate that the school documents that govern the support room are in line with the guideline of the Municipal Education Secretariat of Cuiabá which emphasizes the content of numbers and operations in the work to be developed with mathematics, but in practice, some guidelines regarding referral, diagnosis, grouping of students and teaching methodology are no longer met. In the referrals, the conducting teachers indicate that students do not know how to solve the four operations, mention behavior and personality, but do not describe objectively what are the learning difficulties presented. Likewise, the measures adopted in the classroom to overcome difficulties are not described by teachers. The meanings attributed by students to mathematics are related to their learning of the four basic operations, sometimes present in everyday and work situations in the future. In general, children point out that they have transient learning difficulties in mathematics and highlight playful and dynamic classes as an interesting way to learn mathematics. The support room for students has proved to be another space to perform tasks, and due to the fact that they do not understand what they need to learn or the need for their referral, they end up not making sense of the pedagogical work carried out in SAA.